Requirements Analysis of the Development of Project Based Learning (PJBL)-based Blended Learning Model Assisted by MOOC - Eko Risdianto; Rosane Medriati; Parwito Parwito; Iwan Setiawan (AL-ISHLAH: Jurnal Pendidikan, 2023)
The research aims to determine the needs of students for the PJBL-based blended learning model assisted by MOOC at universities. This type of research is survey research. The research was conducted at a university using a purposive sampling technique with a total of 46 student respondents who were representatives of semester 2, 4, 6, and 8 students. The data collection technique used a questionnaire developed from three aspects: the need for the blended learning model, the need for learning using the MOOC system, and the need for project-based learning. The results of this study indicate that students need a PJBL-based blended learning model using the MOOC system in universities. The results of this research can be used as a basis for development related to the MOOC-assisted project-based blended learning model in further research.